0115 Do Theta Power and other Baseline REM Sleep Parameters Predict Fear Conditioning, Extinction, and Extinction Recall in Healthy Adults?. (27th April 2018) - Germain, A; Lynch, G; Khan, H; McNamee, R; Oh, C; Wallace, M L; Milad, M; Pace-Schott, E F
Abstract: Introduction: REM sleep is reactive to salient experiences and is implicated in affective learning and memory. In addition, acute and chronic changes in REM sleep theta activity and REM density following trauma exposure have been associated with vulnerability or resilience to stress-related psychiatric disorders. Here, we investigated which pre-exposure, baseline REM sleep characteristics might predict or moderate the effect of sleep loss on fear conditioning, extinction learning, and extinction recall in healthy adults. Methods: Healthy adults (n = 172; mean age 23.9 ± 3.4 years; 95 women) completed a baseline overnight polysomnographic (PSG) study. On the following night, participants were randomized to a normal sleep condition, sleep restriction, or sleep deprivation. Fear Conditioning and Extinction Learning occurred in the morning following Night 2. Extinction Recall was tested ~9 hours later, after a full day of continuously monitored wakefulness. Theta activity and other REM sleep parameters were obtained on Night 1. Skin conductance response (SCR) indexed fear responses. Regressions were used to evaluate the independent and potential synergistic effects of sleep group (NS, SR, SD) and baseline REM sleep theta activity and other REM measures parameters on psychophysiological fear responses. Results: Baseline polysomnography and spectral measures did not differ across groups. Frontal theta activity during REM sleep did not independently or synergistically predict the effects of Group on Conditioning, Extinction, or Extinction Recall. REM density independently and positively predicted Conditioning (standardized beta coefficient = .20, t =2.57, p = 0.01). Other REM sleep features did not independently predict or moderate psychophysiological fear responses. Conclusion: In this large sample of healthy young adults, only REM density was independently associated with enhanced discriminative learning during Conditioning. Other baseline REM sleep parameters did not predict the magnitude of fear responses during Extinction or Extinction Recall. REM sleep changes during nights immediately following stress exposure may have better predictive power. Support (If Any): DoD MOMRP Log#11293006 (PI: Germain).